New Advances in the Dairy Industry 2022
DOI: 10.5772/intechopen.101626
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions of Some Minerals Elements in Health and Reproductive Performance of Dairy Cows

Abstract: The dairy business is recognized as an important economic and nutritional resource. The food and agriculture organization (FAO) estimates that there are about 245 million dairy cows in the world. Milk production offers enormous health, sociological, and economic benefits around the world. In emerging economies, livestock serves a range of purposes, including providing a source of household income, a financial asset for women, food security, risk management, and a direct connection to human health. With a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…Trace minerals play pivotal roles in various enzymatic, catalytic, and structural functions in higher vertebrates (Tufarelli et al., 2016). Several environmental and biological factors can impact the concentrations of these substances in the bloodstream of mammals (Fadlalla, 2022). Numerous studies have demonstrated a decrease in serum levels of calcium (Ca), zinc (Zn), magnesium (Mg), phosphorus (P), potassium (K), and selenium (Se) during the pre‐parturient period (Fadlalla, 2022; Shoukat et al., 2022; Ullah et al., 2020; Yadav et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trace minerals play pivotal roles in various enzymatic, catalytic, and structural functions in higher vertebrates (Tufarelli et al., 2016). Several environmental and biological factors can impact the concentrations of these substances in the bloodstream of mammals (Fadlalla, 2022). Numerous studies have demonstrated a decrease in serum levels of calcium (Ca), zinc (Zn), magnesium (Mg), phosphorus (P), potassium (K), and selenium (Se) during the pre‐parturient period (Fadlalla, 2022; Shoukat et al., 2022; Ullah et al., 2020; Yadav et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several environmental and biological factors can impact the concentrations of these substances in the bloodstream of mammals (Fadlalla, 2022). Numerous studies have demonstrated a decrease in serum levels of calcium (Ca), zinc (Zn), magnesium (Mg), phosphorus (P), potassium (K), and selenium (Se) during the pre‐parturient period (Fadlalla, 2022; Shoukat et al., 2022; Ullah et al., 2020; Yadav et al., 2020). Furthermore, they observed that the production of colostrum, fluctuations in feed consumption, and metabolic processes during calving can have an effect on the serum levels of vitamins and trace elements.…”
Section: Introductionmentioning
confidence: 99%
“…I.M.T. Fadlalla et al (2022) argue that a significant number of pathological changes that develop in the body of cattle are somehow associated with manganese deficiency. Attention is paid to the extremely low digestibility of this trace element from inorganic salts.…”
Section: Introductionmentioning
confidence: 99%
“…I.M.T. Fadlalla et al (2022) argue that a significant number of pathological changes that develop in the body of cattle are somehow associated with manganese deficiency. Attention is paid to the extremely low digestibility of this trace element from inorganic salts.…”
Section: Introductionmentioning
confidence: 99%